Galician Music Recording and Associated with it in Buenos Aires (1907-2015) - Pablo Cirio, Norberto (Madrygal. Revista de Estudios Gallegos, 2017)
From data and documentation collected by the author since 1996, we present the landscape of the recording of Galician music and aspects associated to it in Buenos Aires between 1907 and 2015, whose number goes up to 1,540 records. The article analyzes multidirectional strategies between the local recording market, that of this community, and that of territorial Galicia. We also account for their own recording companies, the dozen existing formats, and the types of instrumental configurations in which the 289 existing groups and soloists in the country since 1878 can be classified from a quantitative and qualitative approach, and from a diachronic perspective. Conclusions are elaborated taking into account the characteristics of this primary source and paying special attention to the attribution of symbolic meaning given by producers and consumers of music implicated in the framework of Galician immigration to Argentina.